Analisis Batik Rumah Komar Bandung Pada Kegiatan Modul Nusantara Program Pertukaran Mahasiswa Merdeka Batch 4 - Tira kania pardosi; Feny Silaen; Citra Sianturi; Fitriani Lubis (Populer: Jurnal Penelitian Mahasiswa, 2024)
Since a long time ago, batik has been known and developed in the scope of Indonesian society. Until now batik has been known in the international world which has become an identity of Indonesian national culture. There are many batik motifs from all over Indonesia ranging from western Indonesia to eastern Indonesia. The types of batik produced are divided into 3, namely batik cap, batik tulis, and batik print which are distinguished based on the technique of making batik. Komar Batik is one of the batik cultures in Indonesia. Komar Batik presents the identity of the city of Bandung in a series of contemporary and modern designs. The method used in this study is a qualitative research method with a descriptive qualitative approach. The results showed that there are 2 batik techniques used in komar batik, namely: written batik techniques and stamp batik techniques. Apart from the teserbut technique, there is also the batik print technique. On bat.